2013
DOI: 10.1186/1472-6947-13-s2-s12
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the effectiveness of patient decision aids: key constructs and measurement instruments

Abstract: BackgroundEstablishing the effectiveness of patient decision aids (PtDA) requires evidence that PtDAs improve the quality of the decision-making process and the quality of the choice made, or decision quality. The aim of this paper is to review the theoretical and empirical evidence for PtDA effectiveness and discuss emerging practical and research issues in the measurement of effectiveness.MethodsThis updated overview incorporates: a) an examination of the instruments used to measure five key decision-making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
190
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(198 citation statements)
references
References 56 publications
2
190
0
Order By: Relevance
“…7 Decision aids are provided where there is no obviously right or wrong option, so the focus in evaluating them should not be on the option selected 19 but rather on decision quality defined in terms of knowledge and values-choice agreement. 20 Screening rates may not reflect people"s informed decisions if coercion or obstacles are present. 12 In this study, therefore, our key question was whether evidence-based, consumer-friendly information on overdetection improves the level of informed choice about screening in a community sample of women around the target age for starting breast screening in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…7 Decision aids are provided where there is no obviously right or wrong option, so the focus in evaluating them should not be on the option selected 19 but rather on decision quality defined in terms of knowledge and values-choice agreement. 20 Screening rates may not reflect people"s informed decisions if coercion or obstacles are present. 12 In this study, therefore, our key question was whether evidence-based, consumer-friendly information on overdetection improves the level of informed choice about screening in a community sample of women around the target age for starting breast screening in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Decision quality reflects the extent to which patients are informed and understand their options, and importantly, that decisions made reflect their goals and preferences. 26 With this transition in medical education, providers will likely benefit from learning new skills to improve communication with patients during visits. There are also resources available to support practicing physicians, such as ManagingYourMeds (available from http://managingyourmeds.org), which lists a number of promising medication adherence practices.…”
Section: Person-centered Carementioning
confidence: 99%
“…Kryworuchko, Stacey, Bennett & Graham (2008) concluded that "selecting relevant and high quality outcome measures remains challenging and is an important area for further research in the field of shared decision making" (p.497). Sepucha et al (2013) reviewed 86 studies that utilised instruments that aimed to measure decision making processes and/ or decision quality constructs specific to decision aids. They found that 17 different measurements were used to measure decision making process constructs in these studies, with the Decisional Conflict Scale (DCS) being the most commonly used (n=47).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…They found that not one of the tools in their study measured all key decision making processes and constructs which included decision making process constructs (recognise decision, feel informed about options and outcomes, feel clear about goals and preferences, discuss goals and preferences with healthcare provider, and be involved in decisions), and decision quality constructs (knowledge, realistic expectations, values-choice agreement). Sepucha et al (2013) found that there was no consensus or standardisation of measurement for either the decision making process or decision quality constructs. They concluded that more work was required to develop and evaluate decision aid measurement instruments, and further exploration of theoretical issues to advance future research was urgently required.…”
Section: Implications For Future Researchmentioning
confidence: 99%